Multicentre pilot randomised control trial of a self-directed exergaming intervention for poststroke upper limb rehabilitation: research protocol - Louise Johnson; Paul Bentley; Sara Demain; Jane Burridge; Michelle Broderick; Joe Brereton; Robert O'Shea (BMJ Open, 2024)
Introduction Technology-facilitated, self-directed upper limb (UL) rehabilitation, as an adjunct to conventional care, could enhance poststroke UL recovery compared with conventional care alone, without imposing additional resource burden. The proposed pilot randomised controlled trial (RCT) aims to assess whether stroke survivors will engage in self-directed UL training, explore factors associated with intervention adherence and evaluate the study design for an RCT testing the efficacy of a self-directed exer-gaming intervention for UL recovery after stroke.Methods and analysis This is a multicentre, internal pilot RCT; parallel design, with nested qualitative methods. The sample will consist of stroke survivors with UL paresis, presenting within the previous 30 days. Participants randomised to the intervention group will be trained to use an exergaming device and will be supported to adopt this as part of their self-directed rehabilitation (ie, without formal support/supervision) for a 3-month period. The primary outcome will be the Fugl Meyer Upper Extremity Assessment (FM-UE) at 6 months poststroke. Secondary outcomes are the Action Research Arm Test (ARAT), the Barthel Index and the Modified Rankin Scale. Assessment time points will be prior to randomisation (0–1 month poststroke), 3 months and 6 months poststroke. A power calculation to inform sample size required for a definitive RCT will be conducted using FM-UE data from the sample across 0–6 months time points. Semistructured qualitative interviews will examine factors associated with intervention adoption. Reflexive thematic analysis will be used to code qualitative interview data and generate key themes associated with intervention adoption.Ethics and dissemination The study protocol (V.1.9) was granted ethical approval by the Health Research Authority, Health and Care Research Wales, and the London- Harrow Research Ethics Committee (ref. 21/LO/0054) on 19 May 2021. Trial results will be submitted for publication in peer-reviewed journals, presented at national and international stroke meetings and conferences and disseminated among stakeholder communities.Trial registration number NCT04475692